المسؤولية الاجتماعية ودورها في مساهمة القطاع الخاص في التنمية المستدامة - غدير إبراهيم, ظريفة; عثماني, احلام; الارقط, جهاد (University of eloued جامعة الوادي, 2019)
تهدف هذه الدراسة إلى تحديد مدى القطاع الخاص اعتمدت المؤسسات في ولاية الوادي مفهوم المسؤولية الاجتماعية وتأثير المسؤولية الاجتماعية على القطاع الخاص في تحقيقه التنمية المستدامة لمجتمعهم. اعتمدت الدراسة على المنهج الوصفي على الجانب النظري والطريقة التحليلية التحليلية في الجانب التطبيقي. بناء على طريقة المسح الاجتماعي ، تم استخدام أداة المسح للحصول على آراء عينة الدراسة تتكون من 40 عاملا في هذه المؤسسات. تم تحليل النتائج على SPSS و SPSS عاموس ، تم اختبار نتائج الدراسة باستخدام الأساليب الإحصائية مثل: الاختبارات اللاحقة في حالة الاختلافات ذات الأهمية الإحصائية. وجدنا أن مؤسسات القطاع الخاص في ولاية لا تفعل ذلك المساهمة في تنمية مجتمعهم المحلي ، بسبب نقص تنويع استثماراتهم أوصت الدراسة بضرورة إنشاء مؤسسات القطاع الخاص يدرك دورهم في تحمل المسؤولية تجاه مجتمعهم من خلال الدعم الأنشطة الاجتماعية وتوجيه بعض الاستثمارات ذات الطابع الاجتماعي التي تسهم في خلق فرص عمل ، وبالتالي المساهمة في الحد من البطالة وبالتالي تطوير جميع جوانب التنمية المستدامة. This study aims at identifying the extent to which the private sector institutions in the state of Wadi have adopted the concept of social responsibility and the impact of social responsibility on the private sector in achieving sustainable development for their society. The study was based on the descriptive approach on the theoretical side and the analytical analytical method in the applied side. Based on the method of social survey, the survey tool was used to obtain the views of the study sample consisting of 40 workers in these institutions. The results were analyzed on the SPSS and SPSS Amos, the results of the study were tested using statistical methods such as: Post-tests in the case of differences of statistical significance. We found that the private sector institutions in the Wilayat state do not contribute to the development of their local community, due to the lack of diversification of their investments The study recommended that private sector institutions should be made aware of their role in assuming responsibility towards their society by supporting social activities and directing some investments of a social nature that contribute to the creation of job opportunities, thus contributing to reducing unemployment and thus developing all aspects of sustainable development. Key words: social responsibility, private sector institutions, sustainable development
مذكرة ماستر تخصص اقتصاد وتسيير المؤسسات
Keywords: المسؤولية الاجتماعية ، ومؤسسات القطاع الخاص ، والتنمية المستدامة; social responsibility, private sector institutions, sustainable development